Berobat Kampung: Religion and Traditional Knowledge of Seeking Recovery in Borneo - Yusdiana, Yusdiana; Hariansyah, Hariansyah; Firmansyah, Dedi; Billia, Dini Presti (Pascasarjana IAIN Pontianak, 2023)
This article explores the variants of tradition in seeking recovery within a group of religious community in the upstream Kapuas in Borneo island. It is presented using indigenous psychology, narrative analysis and psycho-anthropology. The data were collected using the techniques of in-depth interviews, psycho-anthropological observations, narrative interpretation and documentation. This work finds that the use of Quranic verses and dhikr as well as religious symbols are are very prominent. The people of the upstream Kapuas river interpret and leave a legacy for traditional healing, beginning with an